ANALISIS PALINOLOGICO DEL HOLOCENO TARDIO DEL SITIO "FORTIN NECOCHEA" (PARTIDO DE GRAL. LAMADRID, PROVINCIA DE BUENOS AIRES, ARGENTINA) (Ameghiniana, 2013)
Pollen analysis showed two types of structures: 1. Originated by analysis of similaritie between models (Q) which allowed to subdivide the profile into three polIen zones (A, B and C). These zones coincide with kown stratigrafic and archaeologic units at the site and 2. originated by interaction of variabls through time (R) which showed three clusters: (I) Ranunculaceae, Plantago and Gramineae which would indicate lower edaphic hurnidity conditions; (lI) Compositae, Umbelliferae, Chenopodiineae, Cyperaceae and Leguminosae which can coexist in flooded places (bogs and or smalI basins); (III) Cruciferae, greatly adapted to different environments, which joins to clusters I and Il at a relatively low similarity level (25%). From these results we postulate a structural model of the ecosystem associated to a pond environment characteristic of Buenos Aires Province from 3.630 + 60 years BP up the present.